Knowledge attribution revisited: a deflationary account - Cresto, Eleonora Beatriz (2018)
According to the usual way of understanding how true knowledge attribution works, it is not right to attribute knowledge of p to S unless p is true and S is justified in believing p. This assumption seems to hold even if we shun away from the idea that we can give an analysis of knowledge in terms of necessary and sufficient conditions. I want to raise some suspicions on the correctness of this traditional picture. I suggest that justification is not always perceived as a necessary condition for true knowledge attribution, according to our pre-theoretical usage of standard epistemic terms. This is not to say that justification is never seen as an important requirement; sometimes it certainly is. Still, the full-fledged, traditional position on epistemic justification needs to be seriously qualified. Ultimately, I will contend that this result lends support to a rival epistemological standpoint — what we might dub a Moderate Peircean stance on epistemic matters.